“Model T” Cells: A Time-Tested Vehicle for Gene Therapy - Kerkar, Sid P. (Frontiers in Immunology, 2013)
T lymphocytes first carried foreign genes safely into humans over two decades ago. Since these pioneering studies, scientific techniques to better understand the genomic landscape of cells has directly led to a more sophisticated appreciation of the diversity, functional complexity, and therapeutic potential of T cells. Through the use of mouse models, we now know the function of the many genes that are critical for T cells to recognize foreign, mutated, or self-antigens and the factors responsible for the lineage diversification of T cells that lead to inhibitory or stimulatory immune responses. This knowledge combined with well-established modalities to introduce genes into T cells allows for the design of effector and memory CD8 and CD4 T lymphocytes specific for viral, fungal, bacterial, parasitic, and tumor-antigens and to design regulatory lymphocytes specific for the self-antigens responsible for autoimmune and inflammatory diseases. Here, I review strategies for designing the ideal T cell by introducing genes controlling (1) the secretion of cytokines/chemokines and their receptors, (2) T-cell receptor specificity, (3) chimeric-antigen receptors that enable for the recognition of surface antigens in an MHC-independent fashion, (4) co-stimulatory/inhibitory surface molecules, and (5) disease defining single-gene factors.